The foreign policies of the Philippines in the period of immobilisme, 1957-1965 - Madrona, Severo Cañete, Jr (Department of History, College of Social Science and Philosophy, University of the Philippines Diliman, 2014)
This dissertation presents a case study in the formulation and implementation of Philippine foreign policy. It examines the factors and reasons on how and why the foreign policies of the Philippines during the period of immobilisme were formulated and implemented from 1957 to 1965. Using the ecological perspective in foreign policy analysis, this dissertation examines the milieu of the period resulting in the formulation and implementation of foreign policies by Presidents Carlos P. Garcia and Diosdado P. Macapagal. Empirical evidence presented here suggests that while Garcia and Macapagal's foreign policies were responsive to the milieu the desired outcomes were not achieved as the personnel implementing the foreign policies had failed to make the policies understood by the international community and the Filipino people.